Analisis Sifat Mekanik dan Struktur Mikro Aluminium Scrap (ADC12) Menggunakan Tungku Listrik - Syaharuddin Rasyid; Arthur Halik Razak; Fahmi Fahmi; Diah Ayu Lestari; Abd. Karim M (Jurnal Teknik Mesin Sinergi, 2019)
Knowing the mechanical and microstructural properties of aluminum scrap materials found in casting using an electric furnace. The research procedure included temperature data (750oC, 800oC, 850oC) and smelting time for 120 minutes. Hardness testing procedure is carried out to get the hardness value from some casting result areas. Microstructure is characterized by a comparison of the grain size of the metal that has undergone casting, to measure the grain size in this study using the image J program. The highest hardness value shows the melting temperature of 800oC with a temperature holding time of 120 minutes of 63.8HB. The longer the temperature holding time, the hardness value will increase. The smallest grain size occurs at a melting temperature of 800oC with a temperature holding time of 120 minutes of 21µm.